Black dog - Pinfold, Levi (Templar Books, 2012)
"When a huge black dog appears outside the Hope family home, each member of the household sees it and hides. Only Small, the youngest Hope, has the courage to face the black dog, who might not be as frightening as everyone else thinks"--